2005
DOI: 10.1002/ptr.1735
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of carotenoids in red paprika, Valencia orange and Golden delicious apple

Abstract: Carotenoid fractions were extracted from red paprika, Valencia orange peel and the peel of Golden delicious apple. Thus, hypophasic carotenoids of paprika (PM1), orange (PM3) and apple (PM4), and epiphasic extractions of paprika (PM2) and apple (PM5) were obtained by extraction, saponification and partition between MeOH-H(2)O (9:1) (hypophasic) and hexane (epiphasic). A high content of capsanthin was quantified in hypophasic carotenoids (PM1) from red spice paprika, whereas the hypophasic fractions from orange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 29 publications
1
21
1
Order By: Relevance
“…Among natural molecules, carotenoids usually are not among the most cytotoxic ones. However, the cytotoxic activity of carotenoids, in particular xanthophylls, has been described in the literature and, in line with the findings that we present herein, this activity is usually higher against cancer cells than against healthy ones [15,16].…”
Section: Cell Assayssupporting
confidence: 89%
“…Among natural molecules, carotenoids usually are not among the most cytotoxic ones. However, the cytotoxic activity of carotenoids, in particular xanthophylls, has been described in the literature and, in line with the findings that we present herein, this activity is usually higher against cancer cells than against healthy ones [15,16].…”
Section: Cell Assayssupporting
confidence: 89%
“…Thus, considerable interest has been focused on alternative/adjuvant approaches such as the use of biologically active compounds, including antioxidants from plants [9]. Several studies demonstrated the inhibitory effects on bacteria of a wide range of fruits, vegetables and their derivatives, such as berries [10], garlic [11][12][13], onion [14], kiwi [15], citrus [16] and wine [17], as well as plant extracts [18] and spices, in particular essential oils [19], cinnamon [20], thyme [21], propolis [22], liquorice [23], red paprika [24], tea [25] and rice [26]. In addition, further studies on the antimicrobial properties of compounds isolated from plant sources, such as resveratrol [27,28], allixin [11], vitamin C [29], ␤-carotene and ␤-tocopherol [9,30] and garcinol [31,32], have given significant information about the existence of potential synergisms among different constituents [33].…”
Section: Introductionmentioning
confidence: 99%
“…Carotenoids, 2,3) lipids and capsaicin 4) have been well studied in the Capsicum species. Now our study has focused on the water-soluble constituents of Paprika and Jalapeño fruits.…”
mentioning
confidence: 99%